Social Dynamics Among Regular Students Toward the Presence of Students with Special Needs in Collaborative Learning in Inclusive Schools - Wida Febriana; Mardhatillah Mardhatillah (Teunuleh Publisher, 2026)
Inclusive education aims to give students with special needs access to learning and affects the social lives of regular students through interactions in diverse classrooms. This study seeks to describe the social dynamics of regular students expected to include students with special needs in collaborative learning at SMP Negeri 18, Malang. The research used a qualitative descriptive method, collecting data through classroom observations, semi-structured interviews, and learning documentation. The subjects were teachers who taught inclusively, Special Education Teachers, regular students, and students identified as having special needs. Data analysis involved data reduction, data presentation, and drawing conclusions, whereas data validity was tested using source and technique triangulation. The findings show that peers do not see students with disabilities as obstacles to learning. Instead, they fostered empathy, tolerance, care, and social responsibility. Teachers view inclusive classrooms as places for character education that improves the academic and social experiences of all students. Regular students often help their peers with special needs by explaining their instructions, completing tasks, or adjusting their pace of work in groups. These results confirm that inclusive classrooms can promote a culture of mutual acceptance and support collaborative learning. This study implies the need to develop teachers' strategies for managing peer interactions, not just adapting the curriculum for students with special needs.